2020
DOI: 10.1101/2020.04.03.022962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host-parasite dynamics set the ecological theatre for the evolution of state- and context-dependent dispersal in hosts

Abstract: While host-parasite interactions are ubiquitous, the large scale consequences of parasite infections are mainly driven by the spatial context. One trait of pivotal importance for the eco-evolutionary dynamics of such metapopulations is the spatial behaviour of hosts, that is, their dispersal. It is well established that dispersal is not a random process, rather dispersal is informed and may depend on internal and external factors. In host-parasite metapopulations, dispersal may be a function of a host’s infect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…In this way, the prey can take the appropriate "decision" to leave or stay in the patch. This condition is also found in a model considering host-parasite context-dependent plasticity (Deshpande et al, 2020). A recent study analysing multiple taxa of invertebrates and vertebrates showed that chemical predator-related cues can induce dispersal, along with alterations in resource availability (Fronhofer et al, 2018).…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…In this way, the prey can take the appropriate "decision" to leave or stay in the patch. This condition is also found in a model considering host-parasite context-dependent plasticity (Deshpande et al, 2020). A recent study analysing multiple taxa of invertebrates and vertebrates showed that chemical predator-related cues can induce dispersal, along with alterations in resource availability (Fronhofer et al, 2018).…”
Section: Introductionmentioning
confidence: 63%
“…x infection prevalence interaction would indicate genetic variation in this plasticity. Finally, we also added population density as a covariate to take into account this potential additional type of context-dependency (Fellous et al, 2012;Deshpande et al, 2020), and we considered experimental block as random factor. We excluded 11 replicates from the state-and context-dependent analysis because no infection was detected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations